Resolvin D1 Attenuates the Organ Injury Associated With Experimental Hemorrhagic Shock. Issue 5 (7th May 2021) - Sordi, Regina; Chiazza, Fausto; Collotta, Debora; Migliaretti, Giuseppe; Colas, Romain A.; Vulliamy, Paul; Brohi, Karim; Dalli, Jesmond; Collino, Massimo; Thiemermann, Christoph
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To evaluate the potential changes in the plasma levels of resolvin D1 (RvD1) in patients with trauma and hemorrhage. Having found that trauma results in a profound reduction in plasma RvD1 in patients, we have then investigated the effects of RvD1 on the organ injury and dysfunction associated with hemorrhagic shock (HS) in the rat. Background: HS is a common cause of death in trauma due to excessive systemic inflammation and multiple organ failure. RvD1 is a member of the resolvin family of pro-resolution mediators. Methods: Blood samples were drawn from critically injured patients (n = 27, ACITII-prospective observational cohort study) within 2 hours of injury for targeted liquid chromatography tandem mass spectrometry. HS rats (removal of blood to reduce arterial pressure to 30 ± 2 mm Hg, 90 minutes, followed by resuscitation) were treated with RvD1 (0.3 or 1 μg/kg intravenous (i.v.)) or vehicle (n = 7). Parameters of organ injury and dysfunction were determined. Results: Plasma levels of RvD1 (mg/dL) were reduced in patients with trauma+HS (0.17 ± 0.08) when compared with healthy volunteers (0.76 ± 0.25) and trauma patients (0.62 ± 0.20). In rats with HS, RvD1 attenuated the kidney dysfunction, liver injury, and tissue ischemia. RvD1 also reduced activation of the nuclear factor (NF)-κB pathway and reduced the expression of pro-inflammatory proteins such as inducible nitric oxide synthase, tumor necrosis factor-α, interleukin-1β, and interleukin-6. Conclusion: Plasma RvD1 is reduced in patients with trauma-HS. In rats with HS, administration of synthetic RvD1 on resuscitation attenuated the multiple organ failure associated with HS by a mechanism that involves inhibition of the activation of NF-κB.